2009
DOI: 10.1161/circgenetics.108.806562
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Familial Clustering of Myocardial Infarction in Patients With Acute Coronary Syndromes

Abstract: Background-Family history of premature myocardial infarction (MI) in first-degree relatives is a risk factor for MI and an indication for primary prevention. Although excess mother-to-daughter "transmission" occurs in ischemic stroke, no published studies have considered sex-of-parent/sex-of-proband interactions in the heritability of MI. Methods and Results-In a population-based study (Oxford Vascular Study) of all patients with acute coronary syndromes (ACS), irrespective of age, family history of all acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…17 We now show that maternal stroke is also a risk factor for MI in women. In men, a maternal history of MI has been shown to be less important than a paternal history of MI, 9 and our findings suggest that the same is true for maternal history of stroke. Previous studies have considered a sex-ofparent effect for FH of MI in MI probands, 26,27 but none have considered FH of stroke in MI probands or been truly population-based or studied sex-of-proband/sex-of-parent effects.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…17 We now show that maternal stroke is also a risk factor for MI in women. In men, a maternal history of MI has been shown to be less important than a paternal history of MI, 9 and our findings suggest that the same is true for maternal history of stroke. Previous studies have considered a sex-ofparent effect for FH of MI in MI probands, 26,27 but none have considered FH of stroke in MI probands or been truly population-based or studied sex-of-proband/sex-of-parent effects.…”
Section: Discussionsupporting
confidence: 60%
“…9 In addition, maternal history of stroke increases risk of stroke in women, 19 and family history of stroke may be a stronger predictor of risk of MI than risk of ischemic stroke. 17 We now show that maternal stroke is also a risk factor for MI in women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 In the OXVASC study, reported family history in an FDR had 83.3% sensitivity and 100% specificity for medical record-confirmed events in the relative. 25 All patients with a diagnosis of ACS or TIA/stroke were enrolled from April 1, 2002, to September 30, 2008, and were eligible for the present study. So that similar numbers of TIA/stroke and ACS events were compared, ACS events until March 31, 2009, were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%